Propositions for teacher training in Accounting - Laffin, Marcos; Hillen, Cristina; Ensslin, Sandra Rolim (Education Policy Analysis Archives, 2018)
The purpose of this study was to identify approaches about teacher education in the accounting area in researches selected, based on Bibliographic Portfolios, theoretical and empirical, related on the subject. Studies by Nossa (1999), Slomski (2007); Slomski & Martins (2008); Miranda, Casa Nova, Cornacchione Júnior (2012), Comunelo et al (2012), Laffin & Gomes (2014, 2016) identify the need for teacher training actions for accounting education. In methodological terms, this study was characterized as qualitative, descriptive and bibliographical. It was done based on the Knowledge Development Process-Constructivist (ProKnow-C) to organize and analyze data and focused on the systematic review stage of the process. It sought to identify gaps and research opportunities related to the object investigated, using the selected Bibliographic Portfolios (PBs). The main conclusion of the study shows that the approaches to teacher training are in the scope of teaching fundamentals, characterized by: teacher knowledge, knowledge base for teaching and reflective teaching. They point to the instrumentalisation of teaching activities related to the objectives and contents of teaching: pedagogical practice, learning environment, didactic transposition, strategies and content of teaching.